STRATEGI PEMERINTAH DAERAH DALAM MENINGKATKAN INVESTASI DI KABUPATEN CIREBON TAHUN 2015 - Mega Dayana Putri; Muhammad Adnan .; Nunik Retno Herawati (Journal of Politic and Government Studies, 2017)
THE GOVERNMENT’S STRATEGIES TO INCREASE INVESTMEN IN THE REGENCY OF CIREBON 2015MEGA DAYANA PUTRI(DEPARTMENT OF GOVERNMENT SCIENCE, FACULTY OF SOSIAL AND POLITICAL SCIENCE, DIPONEGORO UNIVERSITY, SEMARANG)ABSTRACTThis study intends to identify how local governments strategies to increase investments at the Regency of Cirebon in 2015. This research is qualitative-descriptive research, the data have derived from primary sources. To determine informants is executed by snowball sampling method, it intends to determine two types of them. First, the government elements that consists of regent, parliament, BPPT, and BAPPEDA of Cirebon. Second, businessman or investors in Cirebon. For collecting data purposes, the researcher used two method, they are interview and observation method. Data processing techniques consists of data reduction, data presentation, conclusions, and verification, they are executed by a cyclic process.The research result shows that there are four strategies carried out by the Government of Cirebon to attract investments, they are image marketing, attraction marketing, insfrastructure marketing, and people marketing. The four strategies are running smoothly, it is conducted due to social welfare purposes. However, the results have not yet successfuly optimal because none of certainty and clarity rules of the law regarding investment and licensing. This bureaucratic process is considered very complicated. The strategies are only looked at the investment realization, but it does not have significant impact on regional and community development equally.Keywords: regional strategies, local government, investment